Effect of Organo Modified Clays Reinforcement on Thermal Expansion and Degradation Kinetics in Unsaturated Polyester Composites - Niranjana Prabhu, T.; Demappa, T.; Harish, V.; Prashantha, Kalappa (Asian Journal of Chemistry, 2013)
The unsaturated polyester isophthalate (UP) was reinforced with organically modified clay. The composites were analyzed by TGA, TMA, FT-IR, SEM and UL-94 tests. FT-IR spectra show no reaction between clay and polymer matrix. The thermogravimetric analysis indicate the increased thermal resistance when clay particles were introduced into the resin. The Horowitz-Metzger, Freeman-Caroll, Sharp-Wentworth and Friedman kinetic models were used to understand the kinetics of degradation. Degradations were observed to follow these four kinetic models for polymer degradation. Thermal expansion co-efficient and dimension change were found to decrease with increase in the clay loading. Further, Underwriters Laboratories -94 tests conducted on the samples implied that materials can be used for structural applications. UL-94 tests have showed the reduction in burning rate with the increase in clay content. Scanning electron micrographs reveal good dispersion of the clay particles in the matrix.